Answer:
Part 1)
![a=-(1)/(4c^6)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6qbet3b2mxdh79u1gc39y9xjbvctkbj8wn.png)
Part 2)
![a=-(1)/(4c^(-6))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/96we5byokx65lt2pl1ztmsz1giyoakdbie.png)
Explanation:
Part 1) we have
----> equation A
----> equation B
substitute equation B in equation A
![a=2(-(1)/(2)c^(-2))^(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1xu2wsbhprlo9vlwmghuz8sske4vdw6dyv.png)
Applying property of exponents
![(x^(m))^(n)=x^(m*n)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h6s8p8hv5eejltyv8u0oqjbrysbxng6tns.png)
![x^(-m) =(1)/(x^(m))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ccsbirpck31its405pj9fs7gdp3i5gsf1y.png)
![a=2(-(1)/(2)c^(-2))^(3)=2(-(1)/(2))^3(c^(-2))^(3)=2(-(1)/(8))(c^(-6))=-(1)/(4c^6)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9kdqj7y9juczms1xbnujujkn0712wjr24a.png)
therefore
![a=-(1)/(4c^6)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6qbet3b2mxdh79u1gc39y9xjbvctkbj8wn.png)
Part 2) we have
----> equation A
----> equation B
substitute equation B in equation A
![a=2(-(c^(2))/(2))^(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mdqqvqxv0bdzm2vrs4z0gtt5rddhfazl4f.png)
Applying property of exponents
![(x^(m))^(n)=x^(m*n)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h6s8p8hv5eejltyv8u0oqjbrysbxng6tns.png)
![x^(-m) =(1)/(x^(m))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ccsbirpck31its405pj9fs7gdp3i5gsf1y.png)
![a=2(-(c^(2))/(2))^(3)=2(-(c^(6))/(8))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/nnwtf6dujvyzgizazcl09k9fo19ul4ajkf.png)
simplify
![a=-(c^(6))/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/v89spj70i7ckjm36wn397k2flxx15ez6dg.png)
therefore
![a=-(1)/(4c^(-6))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/96we5byokx65lt2pl1ztmsz1giyoakdbie.png)